A preliminary study on the treatment of restaurant wastewater using electrocoagulation technique - Adedotun Temitope Adegoke; Ewemoje Temitayo Abayomi (Journal of Degraded and Mining Lands Management, 2020)
Restaurant Wastewater (RW) is characterized by high volume and strength, with minimal treatment before its release into the environment. Electrocoagulation (EC) could be a better alternative due to its environmental friendliness. The study investigates the use of EC in RW treatment. The samples were collected from the University of Ibadan student Union Building restaurant, between 7-9 am. The EC consisted of an aerator, carbon electrodes, power source, a beaker, and stirrer. Electrodes were connected in mono-polar system at inter-distance of 10 mm, with retention times of 0, 30, 60 and 90 minutes. The RW was aerated before passing direct currents of 0.25, 0.5, 0.75, and 1.0 Amperes. The Colour, Particulate Phosphorus (PP), Soluble Reactive Polyphosphate (PO43-), Phosphorus Pentoxide (P2O5), Chemical Oxygen Demand (COD) and Dissolved Oxygen (DO) were determined. The study was three replicates. Mean percentage removal efficiencies for PP, PO43-, P2O5, COD, DO and colour at 30 minutes (16.85, 19.33, 17.15, 12.58, -32.88 and 20.12%), 60 minutes (30.88, 27.1, 30.57, 21.13, -57.18 and 34.30%), and 90 minutes (40.75, 33.00, 32.83, 25.83, -87.88 and 40.7%) respectively. Better treatment efficiencies of treated wastewater using the electrolytic reactor were obtained with an increase in direct current passing through.